Water utility management. (American Water Works Association, 2005)
Annotation Water utility managers are in a challenging profession, and managerial leadership is key to successful utility operations. AWWA Manual M5, Water Utility Management, was developed through the collaborative effort of leaders in the utility profession who have successfully met the challenges of managing a water utility. This practical manual covers management issues such as internal organizational structure of typical water utilities, government relations, safety programs, engineering, public relations, and more. Book jacket.
Keywords: Waterworks -- Management.; elektronické knihy; electronic books